2022
DOI: 10.7759/cureus.30024
|View full text |Cite
|
Sign up to set email alerts
|

Laser Treatment Modalities for Diabetic Retinopathy

Abstract: Diabetes is a chronic progressive metabolic disorder that is caused by the body's inability to regulate blood glucose levels. If uncontrolled, it can lead to various complications. Among its various complications, longterm diabetes leads to diabetic retinopathy (DR). It is a disease involving blood vessels and the destruction of retinal nerves. It is usually classified into two types: proliferative diabetic retinopathy (PDR) and nonproliferative diabetic retinopathy (NPDR). It progresses and causes loss of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Laser photocoagulation techniques (peripheral retinal laser photocoagulation, focal macular laser photocoagulation, grid photocoagulation) offer a reliable treatment option in proliferative retinopathy, macular oedema and retinal detachment. This type of laser surgery targets the newly formed and abnormal leaking vessels [353,354]. In clinical practice, another surgical technique is vitrectomy which serves for the treatment of vitreous haemorrhages, combined/tractional retinal detachment, macular heterotopia and fibrovascular proliferations [352,355].…”
Section: Device-assisted Minimally Invasive Therapy Plus Drug Applica...mentioning
confidence: 99%
“…Laser photocoagulation techniques (peripheral retinal laser photocoagulation, focal macular laser photocoagulation, grid photocoagulation) offer a reliable treatment option in proliferative retinopathy, macular oedema and retinal detachment. This type of laser surgery targets the newly formed and abnormal leaking vessels [353,354]. In clinical practice, another surgical technique is vitrectomy which serves for the treatment of vitreous haemorrhages, combined/tractional retinal detachment, macular heterotopia and fibrovascular proliferations [352,355].…”
Section: Device-assisted Minimally Invasive Therapy Plus Drug Applica...mentioning
confidence: 99%
“…Perivascular microglia are the unique immune cells of the central nervous system (CNS) and the retina, which play crucial roles in the maintenance of normal vascularization and participate in the inflammation responses of vascular diseases. 4 , 5 Increasing evidence has revealed that the crosstalk between microglia and ECs plays a vital role in systemic inflammation activation, blood-brain barrier (BBB) dysfunction, 6 microvascular impairment, and neuronal degeneration. 7 , 8 , 9 In the healthy tissues, microglia continuously survey their microenvironment and their activation is triggered by a great range of stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…These pathogenic mechanisms play a crucial role in the progression of DR. Additionally, within weeks of the onset of diabetes, leukostasis occurs in the retinal capillaries, leading to capillary occlusion and local ischemia [7]. Retinal hypoxia results in the increased expression of vascular endothelial growth factor (VEGF) [8]. Elevated levels of VEGF induce angiogenesis and enhance retinal vessel permeability, causing disruption of the barrier between the retina and blood [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Retinal hypoxia results in the increased expression of vascular endothelial growth factor (VEGF) [8]. Elevated levels of VEGF induce angiogenesis and enhance retinal vessel permeability, causing disruption of the barrier between the retina and blood [8,9].…”
Section: Introductionmentioning
confidence: 99%